Evaluation of Sexual Assault Cases among Youths Appealed to Muğla Directorate of Forensic Medicine Council - Erbaş, Melike; Kadı, Gülsüm; Balcı, Yasemin; Göçeoğlu, Ümit Ünüvar (The Bulletin of Legal Medicine, 2019)
Objective: The objective was to determine the situation of sexual assault cases among youths, to reveal regional features and to make suggestions by evaluating the cases of youths appealed to Muğla Directorate of Forensic Medicine Council. Material and Method:217 reports were evaluated retrospectively; belonging to the age group of 15-24 years; out of 477 sexual assault cases; that we examined between June 2012 and December 2016. Findings: There were 244 examinations for 217 cases and 71,4% of them belongs to the age group of 15-19 years, 88,9% of them was having Turkish nationality, 91,2% was female and 8,8% was male. The cases were mostly coming from Muğla city center (23,5%) and Marmaris (20,3%). The suspected assailant was ex/new spouse-fiancé-lover for 31,8% of cases, while for 10,6% of cases the suspected assailant was from immediate acquaintances/friends and totally in 85 % of cases the assailant was someone known by the victim. In majority, the crime scene was home (55,3%). For 67,7% of case, the first examination was made in the Directorate of Forensic Medicine Council, for 30,8% of cases the examinations were made in 72 hours. In majority we were asked to write a report about victims if they were physically or psychologically health-impaired or not due to the crime (82%) according to the 102/5 and 103/6 articles of Turkish Penal Code and if the sexual assault happened or not; together with the type of sexual assault (47,5%). Results and Conclusions: Regionally the victims of sexual assault were women in ...